2018
DOI: 10.1021/acs.jpcc.8b04276
|View full text |Cite
|
Sign up to set email alerts
|

Gas Production from the Radiolysis of Water Adsorbed on ZnO Nanoparticles

Abstract: The presence of a metal oxide surface can significantly alter the product yield distribution during the radiolysis of water. Some metal oxides such as ZrO2 or CeO2 have been shown to increase the yield of H2 during the irradiation of water adsorbed on the oxide as compared to liquid water, while other oxides such as PuO2 exhibit lower H2 yields. In this study, the γ-ray radiolysis of the ZnO/H2O system was investigated. Surprisingly, both O2 and H2 were produced in similar quantities. The production of O2 is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Also, with heavier alkali ions, an increased specific surface between the solid matrix and the porous media induced a larger energy transfer to the water and a larger hydrogen production. This observation is similar to transfers observed many in other materials developing an interface with water . A hydrogen production excess can either be induced by the increase in energy absorption coefficient, or by differences in the energy transfer, for example different trapping of electrons by cations clusters.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Also, with heavier alkali ions, an increased specific surface between the solid matrix and the porous media induced a larger energy transfer to the water and a larger hydrogen production. This observation is similar to transfers observed many in other materials developing an interface with water . A hydrogen production excess can either be induced by the increase in energy absorption coefficient, or by differences in the energy transfer, for example different trapping of electrons by cations clusters.…”
Section: Introductionsupporting
confidence: 87%
“…This observation is similar to transfers observed many in other materials developing an interface with water. [24][25][26][27][28][29] A hydrogen production excess can either be induced by the increase in energy absorption coefficient, or by differences in the energy transfer, for example different trapping of electrons by cations clusters.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to have a solid surface to split water for hydrogen production during radiolysis. [14][15][16] The kinetics of molecular hydrogen on the surface of different polymorphs of Al 2 O 3 at different temperatures was studied. The optimization of the experimental conditions is summarized below.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the energy carriers' migration in radiation-catalytic active oxides varies at different intervals depending on the oxides composition, their structural regularity and electrophysical characteristics. Therefore, the effective energy transfer distance in radiation-catalytic active oxides is limited by these interval dimensions, which in turn shows the radiationcatalytic activity, which again depends on the particle size [3][4][5][6][7][8]. Nano-ZrO2 has good thermal insulation and dielectric properties over a wide temperature range, which allows it to be considered as a promising material in the field of microelectronics and the use of construction materials [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%